2013
DOI: 10.1002/jobm.201200617
|View full text |Cite
|
Sign up to set email alerts
|

Differential antibacterial properties of the MurA inhibitors terreic acid and fosfomycin

Abstract: Terreic acid is a metabolite with antibiotic properties produced by the fungus Aspergillus terreus, but its cellular target remains unknown. We recently reported that terreic acid inactivates the bacterial cell wall biosynthetic enzyme MurA in vitro by covalent reaction with residue Cys115 in a similar manner as the MurA-specific antibiotic fosfomycin. To address if terreic acid also targets MurA in vivo, we conducted antibacterial studies using selected E. coli strains in parallel with fosfomycin. While overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…A small molecule inhibitor of MurG that augments the activity of β-lactams against methicillin-resistant Staphylococcus aureus was recently identified (141). MurA has been a popular target for the design of novel antibiotics, and several inhibitors of MurA have been identified that are active against various bacterial species (87,(142)(143)(144)(145)(146)(147). The chokepoint enzyme glucose-1-phosphate thymidylyltransferase (rfbA/rmlA), involved in O antigen biosynthesis, is also a target in Streptococcus pneumoniae (148) and Pseudomonas aeruginosa (149).…”
Section: Discussionmentioning
confidence: 99%
“…A small molecule inhibitor of MurG that augments the activity of β-lactams against methicillin-resistant Staphylococcus aureus was recently identified (141). MurA has been a popular target for the design of novel antibiotics, and several inhibitors of MurA have been identified that are active against various bacterial species (87,(142)(143)(144)(145)(146)(147). The chokepoint enzyme glucose-1-phosphate thymidylyltransferase (rfbA/rmlA), involved in O antigen biosynthesis, is also a target in Streptococcus pneumoniae (148) and Pseudomonas aeruginosa (149).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have mentioned that the overexpression of the murA gene can greatly increase the MICs of fosfomycin, the difference in murA expression between fosfomycin-sensitive and fosfomycin-resistant S. aureus has not been reported ( Garcia et al, 1995 ; Olesen et al, 2014 ). In the current study, the results of qRT-PCR revealed a significant difference between the fosfomycin-resistant and fosfomycin-susceptible S. aureus with respect to the expression of murA as compared with that of S. aureus ATCC 29213.…”
Section: Discussionmentioning
confidence: 99%
“…Terreic acid (catalog number SML0480, Sigma-Aldrich, St. Louis, MO, USA) was dissolved in saline and administered intraperitoneally at doses of 0, 3.75, 5, 7.5, or 15 mg/kg. These doses have been shown to have anti-inflammatory, antimicrobial, and anti-tumor actions (Han et al, 2010;Kawakami et al, 1999;Kawakami et al, 2007;Olesen et al, 2014;Yamamoto et al, 1980). Pergolide mesylate salt (catalog number P8828, Sigma-Aldrich) was dissolved in saline and administered intraperitoneally at doses of 0, 1, 2, or 4 mg/kg.…”
Section: Drugsmentioning
confidence: 99%